1980
DOI: 10.1007/bf01869460
|View full text |Cite
|
Sign up to set email alerts
|

Microprobe study of toad urinary bladder in absence of serosal K+

Abstract: The bulk of the intracellular potassium in mucosal epithelial cells from toad urinary bladder has been previously reported to exchange very slowly with the serosal medium, with a half-time of some 9 hr. This observation, based on chemical analyses of mucosal cell scrapings, has been reexamined with stimultaneous diffractive and energy dispersive electron probe X-ray microanalysis. Fifty-three intracellular sites in hydrated sections and 286 sites in dehydrated sections were studied in bladders from eight toads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
15
1

Year Published

1980
1980
1992
1992

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 42 publications
3
15
1
Order By: Relevance
“…Taken together with previously published estimates of the changes in total ionic contents induced by potassium depletion (Robinson & Macknight, 1976a), these data led to the suggestion that potassium might be accumulated by a sodium-independent mechanism. Recent electronmicroprobe analysis of toad bladder is in qualitative agreement with previous estimates based on chemical analysis of mucosal cell scrapings, but indicates that 0022-2631/80/0057-0235 $01.40 9 1980 Springer-Verlag New York Inc. more sodium is actually gained by the transporting epithelial cells than had previously been estimated; the accumulation of sodium and loss of potassium are comparable in magnitude (Civan, Hall & Gupta, 1980). Thus, given the uncertainties of the experimental techniques, and the possibility that the stoichiometry of the pump might undergo modest changes even under physiologic conditions, the dissociation between the time courses of intracellular potassium activity and short-circuit current noted by DeLong and Civan (1978) might be consistent with the operation of a single Na-K rheogenic pump at the basolateral membrane.…”
supporting
confidence: 71%
See 4 more Smart Citations
“…Taken together with previously published estimates of the changes in total ionic contents induced by potassium depletion (Robinson & Macknight, 1976a), these data led to the suggestion that potassium might be accumulated by a sodium-independent mechanism. Recent electronmicroprobe analysis of toad bladder is in qualitative agreement with previous estimates based on chemical analysis of mucosal cell scrapings, but indicates that 0022-2631/80/0057-0235 $01.40 9 1980 Springer-Verlag New York Inc. more sodium is actually gained by the transporting epithelial cells than had previously been estimated; the accumulation of sodium and loss of potassium are comparable in magnitude (Civan, Hall & Gupta, 1980). Thus, given the uncertainties of the experimental techniques, and the possibility that the stoichiometry of the pump might undergo modest changes even under physiologic conditions, the dissociation between the time courses of intracellular potassium activity and short-circuit current noted by DeLong and Civan (1978) might be consistent with the operation of a single Na-K rheogenic pump at the basolateral membrane.…”
supporting
confidence: 71%
“…Initial estimates of the relative gain in sodium and loss of potassium (Robinson & Macknight, 1976a) had suggested that insufficient intracellular sodium was available following potassium depletion to sustain potassium accumulation by the Na -K exchange pump. The more recent microprobe data of Civan et al (1980) have indicated that the redistributions in sodium and potassium are comparable in magnitude, so that it is no longer necessary to invoke an additional transport mechanism responsible for cellular potassium accumulation.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations